2009
DOI: 10.1021/jf902441n
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Environmental Effects on Coffee (Coffea arabicaL.) Bean Fatty Acid Profile: Impact on Variety and Origin Chemometric Determination

Abstract: In a previous study, the effectiveness of chlorogenic acids, fatty acids (FA), and elements was compared for the discrimination of Arabica varieties and growing terroirs. Since FA provided the best results, the aim of the present work was to validate their discrimination ability using an extended experimental design, including twice the number of location x variety combinations and 2 years of study. It also aimed at understanding how the environment influences FA composition through correlation analysis using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
7
45
0
2
Order By: Relevance
“…The hypothesis is that volatile compounds in green coffee represent a signature of the biochemical composition of coffee beans and its development in the last weeks prior to ripening. In previous studies (Villarreal et al, 2009;Joët et al, 2010), we already showed that variations in coffee bean aroma precursor composition were temperature-dependent.…”
Section: Temperatures During Seed Development Affect Volatile Compoundsmentioning
confidence: 80%
“…The hypothesis is that volatile compounds in green coffee represent a signature of the biochemical composition of coffee beans and its development in the last weeks prior to ripening. In previous studies (Villarreal et al, 2009;Joët et al, 2010), we already showed that variations in coffee bean aroma precursor composition were temperature-dependent.…”
Section: Temperatures During Seed Development Affect Volatile Compoundsmentioning
confidence: 80%
“…They are based on the determination of different compounds, e.g., volatile compounds, caffeine, tannins and polyphenols, lipids, individual carbohydrates like sucrose, glucose, fructose, arabinose, galactose, polysaccharides like cellulose, amino acids, vitamins B3 and PP, chlorogenic acid, trigonelline, and minerals (Bernal et al 1996;Costa Freitas and Mosca 1999;Anderson and Smith 2002;Villarreal et al 2009;Hecimovic et al 2011;Wei et al 2011). These chemical species are often measured for the purpose of discriminating coffee varieties and brands or determinting the coffee origin (Bernal et al 1996;Costa Freitas and Mosca 1999;Anderson and Smith 2002;Villarreal et al 2009;Hecimovic et al 2011). However, it should be considered that all stages involved in the production of coffee, from coffee harvesting to roasting, can change the composition of the final product (Anderson and Smith 2002;Mussatto et al 2011).…”
Section: Elemental Coffee Analysismentioning
confidence: 99%
“…It is directly affected by environmental aspects, of both natural and human origin (Avelino et al, 2005;Camargo, 2010;Villarreal et al, 2009;Bertrand et al, 2008).The great variety of coffee types in Brazil is due to cultivation in diverse regions of the country, under the characteristic climatic conditions of each location.…”
Section: Introductionmentioning
confidence: 99%